(untitled) (Aintelia Science Notes, 2022)
The investment planning of the distribution network has evolved significantly the emergence of distributed energy resources (DEKs) with generated demand, rapid technological advanced in energy storage system, and rising consumer expectations. Nowadays, planning of active distribution systems (ADS) has been an important issue. There are numerous extensive literatures on ADS planning. This paper reviews the current state of distribution planning. Firstly, traditional investment plans made in Turkey and the approach to ADS are examined, ADS studies conducted in other countries, outputs and case studies are examined. Secondly, the effects of DECs on ADS planning are investigated. The features of ADS planning and the factors affecting ADS are outlined. Finally, it explores some aspects of ADS planning research, including planning within all the elements combined in ADS.